EVALUASI KINERJA DAN RENCANA PERKUATAN RANGKA ATAP GEDUNG GEREJA KATEDRAL JAYAPURA PASCA GEMPA JAYAPURA 2023 - Dualembang, Hery; Paseru, Riswandy Loly (Universitas Teuku Umar, 2025)
The majority of areas in Indonesia, such as the city of Jayapura, are categorized within zones of moderate to high seismic intensity. On February 9, 2023, a 5.4 magnitude earthquake hit Jayapura, resulting in damage to various structures, including the Cathedral Church. Assessments conducted after the earthquake revealed structural issues, including cracks in walls and significant deflection in the roof truss system. From the structural assessment of the current roof, it was determined that eleven truss elements had failed, and every rafter showed deflection surpassing the permissible limit of L/240. The reinforcement involved steel elements and created a Cremona truss framework with WF 250.125.6.9 and UNP 75.40.5 profiles. Connections were established with chemical anchors and endplates between the steel profiles and 30×50 cm concrete beams, along with welded joints linking the steel elements. Evaluation results indicated that the enhanced structure achieved a secure performance level and complied with applicable, especially SNI 1729:2020 for structural steel design. This situation emphasizes the significance of evaluating buildings after an earthquake and implementing specific reinforcement strategies to regain structural stability and safety.Keywords— steel, performance evaluation, earthquake, reinforcement.